Parenting Education and Preventing Stunting Through Leaflet Media for Pregnant Women in Tabunganen Kecil Village - Noor Baiti (Borneo Community Development, 2022)
Income, sanitation, clean environment, nutritious food and parents' understanding of food and nutritional intake during pregnancy are one of the factors causing stunting. This activity was carried out in the Tabunganen Kecil area with the target of 5 pregnant women. This activity is carried out using the lecture method or the delivery of material using leaflets. The purpose of the implementation is to provide parenting education and prevent stunting for pregnant women through leaflet media in Tabungaen Kecil Village. The media is designed with simple and colorful language so that parents can better understand the meaning of stunting prevention and help parents understand and apply it in everyday life. The result of this activity is that parents can understand the meaning of the material presented with parenting, compassion and hone as well as an understanding of stunting prevention for pregnant women by increasing nutrition and nutritional intake during pregnancy and maintaining the baby's nutrition in kandunan and after giving birth